Analisis Framing Penulisan Pemberitaan Tragedi Kerusuhan Stadion Kanjuruhan Malang di Kompas.id - Syahrul Ferdian; Lina Wati; Alamsyah Alamsyah (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Recently, the club from Malang is facing sad news. Several mass media reported an event about Indonesian football over the tragedy of riots in the Liga 1 Indonesia match at Malang's Kanjuruhan Stadium which is the home of the Arema FC club. The riot occurred when the match between Arema FC and Persebaya Surabaya was held on Saturday, October 1, 2022, at 20.00.. When the incident happened, it had shocked the world of football. Some media began to change the headline of the news into a riot event at Malang's Kanjuruhan stadium. One of them is Kompas.id media, where media journalists Kompas.id shape and frame an event that will later become a headline in their media. So this study aims to find out how the writing of media journalists Kompas.id through Syntactic, Script, Thematic and Rhetorical Structures in framing the tragedy of the riot at Malang's Kanjuruhan Stadium which will later be used as a report. The method used in this study is a descriptive qualitative method with framing analysis of Zhong Dang Pan and Gerald M. Kosicki models. The results of this study show that journalists Kompas.id in framing the tragedy of the riot at Malang's Kanjuruhan Stadium more prominent information related to the causes and mistakes committed by security forces and the organizing committee in the content of the news text with different discussion themes in each report, so that the news led to this opinion ofthe public who viewed The image of the police and the organizing committee is also bad for the community. It can be seen from the four framing structures observed in this study, namely (Syntax, Script, Thematic, Rhetorical).